Orthodontic treatment of relapse using the preinserted endosseous dental implants - Güliz Aktas; Hakan El; Hilal Kan; İlgar Adiloglu; İlken Kocadereli (Cumhuriyet University, 2011)
In contemporary dentistry, endosseous implants are widely used to replace missing teeth with a survival rate of 90-95%. They have been accepted in the literature as a very good alternative to conventional prosthetic restorations. With a proper diagnosis and treatment plan, osseointegrated implants can also be used as an absolute anchorage in order to obtain orthodontic tooth movement. The aim of this case report is to present the multidisciplinary treatment of a patient whose teeth were relapsed after comprehensive orthodontic treatment and endosseous implant insertion. A 16 year -old caucasian female patient with two congenitally missing lateral incisors and retrognathic maxilla had been treated with fixed orthodontic appliances. Treatment plan consisted of space opening for lateral incisors and leveling and aligning the dental arches. Following the orthodontic therapy 2 endosseous implants were inserted and Hawley retainers were fabricated and prescribed for full time wear. During the osseointegration period of the implants patient did not use the retainers and a relapse occured as a result. After consultation with the prosthodontists dental implants were decided to be used as anchorage unit to align the relapsed teeth and detail the occlusion. Temporary crowns were fabricated over the implants and maxillary teeth were banded and bonded. After 6 months of treatment an acceptable occlusion was reestablished. The stability of the dental implants were not affected during the orthodontic force application. Full length porcelain veneer crowns were inserted at the end of orthodontic treatment. Vertical loading of an implant produces the lowest stress to the supporting bone. When the implants are used as an anchorage unit, formation of a horizontal force vector due to rotational moments is inevitable. However, weak horizontal forces (25-50 gr.) in order to obtain tooth movement did not affect the stability of the dental implants.